2020
DOI: 10.1038/s41386-019-0595-1
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk for Alzheimer's disease shapes hippocampal scene-selectivity

Abstract: Preclinical models of Alzheimer's disease (AD) suggest APOE modulates brain function in structures vulnerable to AD pathophysiology. However, genome-wide association studies now demonstrate that AD risk is shaped by a broader polygenic architecture, estimated via polygenic risk scoring (AD-PRS). Despite this breakthrough, the effect of AD-PRS on brain function in young individuals remains unknown. In a large sample (N = 608) of young, asymptomatic individuals, we measure the impact of both (i) APOE and (ii) AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…However, contrary research findings have been reported between the AD-PRS and hippocampal activation. Chandler et al ( 2020 ) found a significantly positive correlation and Xiao et al ( 2017 ) found a significantly negative correlation during the episodic memory. This divergence may be due to the different task codings and sample size of the studies.…”
Section: Associations Of Ad-prs With Neuroimaging Biomarkersmentioning
confidence: 98%
“…However, contrary research findings have been reported between the AD-PRS and hippocampal activation. Chandler et al ( 2020 ) found a significantly positive correlation and Xiao et al ( 2017 ) found a significantly negative correlation during the episodic memory. This divergence may be due to the different task codings and sample size of the studies.…”
Section: Associations Of Ad-prs With Neuroimaging Biomarkersmentioning
confidence: 98%
“…fMRI studies of hippocampal activation during memory tasks have shown both hypo- (15)(16)(17) and hyper-activation (18-23) in individuals with mild cognitive impairment (MCI) or AD compared to controls. Hippocampal hyper-(24-28) and hypo-activation (29) have also been reported in cross-sectional studies of healthy APOE ε4 allele carriers relative to non-carriers, and as a function of increased AD PRS (30,31).…”
Section: Introductionmentioning
confidence: 77%
“…Based on previous studies showing effects of AD PRS on cognitive decline (9) and level of hippocampal functioning in healthy aging (30,31), we hypothesized that AD PRS would also predict decline in hippocampal activation. However, we did not observe such an effect for any of our three selected PRS pvalue thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…The associations of polygenic scores with memory and cognitive function imply possible alterations of brain structure and functions. Several studies have examined the associations between AD polygenic risk and MRI findings ( Sabuncu et al, 2012 ; Habes et al, 2016 ; Harrison et al, 2016 ; Mormino et al, 2016 ; Nho et al, 2016 ; Desikan et al, 2017 ; Foley et al, 2017 ; Hayes et al, 2017 , 2020 ; Xiao et al, 2017 ; Ge et al, 2018 ; Kauppi et al, 2018 ; Li et al, 2018 ; Chandler et al, 2019 ; Tan et al, 2019 ; Wang et al, 2019 ; Altmann et al, 2020 ; Matloff et al, 2020 ; Zhou et al, 2020 ), fMRI findings ( Xiao et al, 2017 ; Axelrud et al, 2019 ; Chandler et al, 2020 ), and PET imaging findings ( Mormino et al, 2016 ; Darst et al, 2017 ; Ge et al, 2018 ; Porter et al, 2018a , b , c ; Tan et al, 2018 , 2019 ; Leonenko et al, 2019a ; Altmann et al, 2020 ).…”
Section: Polygenic Score Models For Predicting Brain Statusmentioning
confidence: 99%
“…In addition to structural changes, AD polygenic risk might be associated with brain Aβ load ( Mormino et al, 2016 ; Darst et al, 2017 ; Porter et al, 2018a , c ; Tan et al, 2018 , 2019 ; Leonenko et al, 2019a ; Altmann et al, 2020 ) as measured by PET imaging. Moreover, several studies discuss the possible effects of polygenic risk on brain functional changes including hippocampal activation ( Xiao et al, 2017 ; Chandler et al, 2020 ) and connectivity between specific brain regions ( Axelrud et al, 2019 ), providing additional evidence for the effects of AD polygenic risk on brain function. Meanwhile, Aβ measured by PET imaging has been introduced to stratify AD patients prior to PRS evaluation ( Porter et al, 2018b ).…”
Section: Polygenic Score Models For Predicting Brain Statusmentioning
confidence: 99%